10. Upaya Penanganan Kejahatan Lingkungan Pembakaran Hutan dan Lahan Gambut di Sumatera 2004-2015 - Suryadi, Muhammad; Putranti, Ika Riswanti; Paramasatya, Satwika (Journal of International Relations, 2017)
Forest fires in Sumatera which occurs almost every year has become a major problem for Indonesia that need to be resolved. The forest fires is purposely caused by the corporates’ activities which use fires in their land clearing method. On one hand, Indonesia has tried to overcome the problem by creating legal base as the policy to restrict fire utilization for land clearing method done by the corporates. On the other hand, as the primary purpose of corporates is under economic reason for gaining profit, the idea of extracting nature sustainably without interfering ecological balance has not been completely understood. This situation has become a concern regional by ASEAN as it has created serious effect towards other member of states’ territory. In 2002 ASEAN established ASEAN Agreement on Transboundary Haze Pollution (AATHP) as a environmental regime which its purposes is to prevent and monitor transboundary haze pollution as a result of land and/or forest fires through concerted national efforts also intensified regional and international co-operation. Using environmentalism perspective and negotiated environmental agreement, this research shall analyze the problem faced by Indonesia’s government and give its recommendation in the form of creating an environmental protection agreement among the corporates and the civilians.